The Effects of Graphic Structure on Young Children's Visual Narrative Comprehension. - Johnson, Colin. (2017)
Abstract: Scholars of children's picture books and theorists of visual communication argue that every feature - or graphic structure - on a visual surface functions to communicate meaning to the viewer. In turn, the viewer actively constructs meaning from the information presented. This study examined how manipulating graphic structures in illustrations affected children's comprehension of a wordless picture book. 26 4- to 7-year-old children viewed either a simple version of an original book - with black and white line drawings of only central figures - or a complex version - with colorful figures and richly detailed backgrounds. Children then participated in a traditional narrative comprehension procedure. Children who viewed the simple version made more spontaneous inferences and were more attune to character states and emotions. On the other hand, children who viewed the complex version were more responsive to the book and more successful at constructing a narrative from the pictures. Discussion focuses on how these findings relate to existing visual communications theories, and proposes a preliminary model for children's meaning-making of visual media.; Thesis (M.A.)--Tufts University, 2014.; Submitted to the Dept. of Child Development.; Advisor: Calvin Gidney III.; Committee: Martha Pott, and Heather Urry.; Keywords: Reading instruction, Early childhood education, and Multimedia.